2021
DOI: 10.3389/fmicb.2021.719877
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Lonicera japonica Extracts in Animal Production: From the Perspective of Intestinal Health

Abstract: Lonicera japonica (L. japonica) extract is rich in active substances, such as phenolic acids, essential oils, flavones, saponins, and iridoids, which have a broad spectrum of antioxidant, anti-inflammatory, and anti-microbial effect. Previous studies have demonstrated that L. japonica has a good regulatory effect on animal intestinal health, which can be used as a potential antibiotic substitute product. However, previous studies about intestinal health regulation mainly focus on experimental animals or cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 165 publications
(293 reference statements)
0
36
0
Order By: Relevance
“…In addition, the immune and inflammatory response is closely associated with intestinal barrier function [ 52 , 53 ]. sIgA, an immunoglobulin secreted by plasma cells of the intestinal mucosa, is a major effector of the intestinal mucosal immunity, which acts as the first defense line to prevent the colonization of pathogens in the intestinal mucosa and plays an important role in local anti-infection of the body [ 24 , 54 ]. Our results from the present study showed that the sIgA content in jejunum mucosa significantly decreased when piglets suffered from IUGR, which indicated that IUGR damages the intestinal immune function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the immune and inflammatory response is closely associated with intestinal barrier function [ 52 , 53 ]. sIgA, an immunoglobulin secreted by plasma cells of the intestinal mucosa, is a major effector of the intestinal mucosal immunity, which acts as the first defense line to prevent the colonization of pathogens in the intestinal mucosa and plays an important role in local anti-infection of the body [ 24 , 54 ]. Our results from the present study showed that the sIgA content in jejunum mucosa significantly decreased when piglets suffered from IUGR, which indicated that IUGR damages the intestinal immune function.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota maintains a symbiotic relationship with the host and regulates several important functions including host metabolism, nutrients digestion and absorption, immunity, and intestinal barrier function (5,29). So, the dynamic balance of intestinal microbiota is crucial for animal intestinal health, while optimum intestinal health is crucial to animal growth and health (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the dynamic balance of intestinal microbiota is of prime importance to animal growth and health. However, many factors can cause microbial imbalances in the gastrointestinal tract, which may seriously affect nutrients' utilization and host health (3)(4)(5). Gut microbiota diversity and composition in humans as well in animals can be modulated by nutritional strategies, such as changes in dietary composition and the addition of feed additives (3,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 300 compounds from the LJF extract including volatile oils, organic acids, and flavonoids have been identified ( Tang et al, 2021 ). Chlorogenic acid and luteolin are used as quality control standards for the characterization of medical materials ( Yuan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%